Post-Keynesianism and Latin American structuralism: there and back again - Manna, João Vicente Novaes Camargo (2024)
Throughout history, economic development has been studied by different schools of thought. The literature on development economics was established mainly in the 1950s and has developed over the decades, with different analyses from distinct schools of economic thought. Between the 1950s and 1970s, contributions from different groups of authors stood out in the field of development economics, such as neoclassicals, post-Keynesians, and the so-called pioneers in development. This dissertation develops an analysis focusing on the last two groups. Regarding the development pioneers, this work focuses more specifically on the theoretical contributions of Latin American structuralism. The main objective of this work is to analyze two movements of theoretical influences throughout three essays. The first is the influence of post-Keynesian thought on Latin American structuralist thought. This analysis is based mainly on the works of the structuralist Celso Furtado and the post-Keynesian Nicholas Kaldor from the 1950s and 1960s. The second theoretical movement analyzed in this dissertation is the influence of Latin American structuralist thought on post-Keynesian thought. This is done mainly based on the literature on post-Keynesian growth models, starting with Anthony Thirwall\'s seminal contribution in the late 1970s and reaching Engelbert Stockhammer\'s recent proposal of 2023 (of a post-Keynesian-structuralist approach) in a movement in which the post-Keynesian school absorbs classical theoretical concepts of Latin American structuralism. To study these two movements, the theoretical developments of these two schools of thought are mapped, considering theoretical, methodological, and historical aspects.